Исследование зольника 10 на Западном укреплении Бельского городища в 2008 г. - Шрамко, И.Б. (Археологічні дослідження в Україні, 2009)
The paper presents materials of new research on the burnt mound 10 of the Western fortification of Bilsk hill-fort. Several husbandry complexes, remains of a room, animal sacrifices, numerous and various Early Scythian period materials have been discovered on the area studied, as well as an excavation trench of V.O. Horodtsov, who studied the hill-fort in 1906, was found.